Antimicrobial Protection of Marsupial Pouch Young - Cheng, Yuanyuan; Belov, Katherine (Frontiers in Microbiology, 2017)
Marsupials diverged from eutherian mammals about 148 million years ago and represent a unique lineage of mammals with distinctive morphological and reproductive characteristics. Marsupials have significantly shorter gestation periods than eutherians. Pregnancy typically ranges from 15 to 35 days, with young being born at a very early developmental stage and lacking differentiated lymphoid tissues and mature effector cells. Recent microbiome studies of the marsupial pouch revealed that marsupial young can face intense microbial challenges after birth, as the pouch contains a broad range of Gram-positive and Gram-negative bacteria. Antimicrobials are believed to play a significant role in the immune protection of marsupial newborns during their pouch life. The skin of the postreproductive pouch secretes antimicrobial lysozyme and dermcidin, which may contribute to the decreased density of certain bacteria in the pouch. A range of antimicrobial agents, such as immunoglobulins, lysozyme, transferrin, and cathelicidins, have been identified in marsupial milk. Antimicrobial assays have revealed that marsupial cathelicidins have broad-spectrum activity against a variety of bacteria and fungi, including several multi-drug resistant strains. In this article, we will review the action mechanisms of these antimicrobial compounds and discuss how they protect marsupial newborns from potentially pathogenic bacteria inside the pouch. We will also discuss the potential of marsupial antimicrobial compounds as a source of novel antibiotics.